Diels–Alder reactions of myrcene using intensified continuous-flow reactors - Hornung, Christian H.; Álvarez-Diéguez, Miguel Á.; Kohl, Thomas M.; Tsanaktsidis, John (Beilstein Journal of Organic Chemistry, 2017)
This work describes the Diels–Alder reaction of the naturally occurring substituted butadiene, myrcene, with a range of different naturally occurring and synthetic dienophiles. The synthesis of the Diels–Alder adduct from myrcene and acrylic acid, containing surfactant properties, was scaled-up in a plate-type continuous-flow reactor with a volume of 105 mL to a throughput of 2.79 kg of the final product per day. This continuous-flow approach provides a facile alternative scale-up route to conventional batch processing, and it helps to intensify the synthesis protocol by applying higher reaction temperatures and shorter reaction times.
Keywords: continuous processing; flow chemistry; renewable feedstock; surfactant

(untitled) - Romeo, L. M.; Catalina, D.; Lisbona, P.; Lara, Y.; Martínez, A. (Greenhouse Gases: Sci. Technol., 2011)

(untitled) - Gallezot, P. (Catal. Today, 2007)

(untitled) - Behr, A.; Johnen, L. (ChemSusChem, 2009)

(untitled) - Wilden, K.-G.; Alanko, P.; Uotila, M. (Ann. Bot. Fenn., 1977)

(untitled) - Fekam Boyom, F.; Amvam Zollo, P. H.; Menut, C.; Lamaty, G.; Bessière, J. M. (Flavour Fragrance J., 1996)

(untitled) - Abaul, J.; Bourgeois, P.; Bessiere, J. M. (Flavour Fragrance J., 1995)

(untitled) - Bonaga, G.; Galletti, G. C. (Anal. Chim. Acta, 1985)

Spices, Flavour Chemistry and Antioxidant Properties - Shu, C.-K.; Lawrence, B. M. (Reasons for the Variation in Composition of Some Commercial Essential Oils, 1997)

(untitled) - Orav, A.; Kailas, T.; Jegorova, A. (Proc. Est. Acad. Sci., Chem., 2003)

(untitled) - Verma, M. K.; Anand, R.; Chisti, A. M.; Kitchlu, S.; Chandra, S.; Shawl, A. S.; Khajuria, R. K. (J. Essent. Oil-Bear. Plants, 2010)

U.S. Patent - Goldblatt, L. A.; Palkin, S. (Process for converting nopinene to myrcene, 1947)

U.S. Patent - Dahill, R. J., Jr (Myrcene-methacrylonitrile adducts, 1973)

WO Patent - Tabor, R.; Bernhardt, R. J.; Luxem, F. J.; Yao, C.; Wallace, G. J. (Surfactants and Solvents Containing Diels-Alder Adducts, 2013)

Green and Sustainable Medicinal Chemistry - Blacker, A. J.; Breen, J. R.; Bourne, R. A.; Hone, C. A. (The Growing Impact of Continuous Flow Methods on the Twelve Principles of Green Chemistry, 2016)

(untitled) - Ley, S. V.; Fitzpatrick, D. E.; Ingham, R. J.; Myers, R. M. (Angew. Chem., 2015)

(untitled) - Myers, R. M.; Fitzpatrick, D. E.; Turner, R. M.; Ley, S. V. (Chem. – Eur. J., 2014)

(untitled) - Elvira, K. S.; Casadevall i Solvas, X.; Wootton, R. C. R.; deMello, A. J. (Nat. Chem., 2013)

(untitled) - Wiles, C.; Watts, P. (Green Chem., 2012)

(untitled) - Watts, P.; Wiles, C. (J. Chem. Res., 2012)

Microreactors: New Technology for Modern Chemistry - Ehrfeld, W.; Hessel, V.; Löwe, H. (Wiley-VCH Verlag GmbH, 2000)

(untitled) - Baxendale, I. R.; Hornung, C.; Ley, S. V.; de Mata Muñoz Molina, J.; Wikström, A. (Aust. J. Chem., 2013)

(untitled) - Micic, N.; Young, A.; Rosselgong, J.; Hornung, C. H. (Processes, 2014)

(untitled) - Hornung, C. H.; Guerrero-Sanchez, C.; Brasholz, M.; Saubern, S.; Chiefari, J.; Moad, G.; Rizzardo, E.; Thang, S. H. (Org. Process Res. Dev., 2011)

(untitled) - Hornung, C. H.; Mackley, M. R.; Baxendale, I. R.; Ley, S. V. (Org. Process Res. Dev., 2007)

(untitled) - McMullen, J. P.; Jensen, K. F. (Org. Process Res. Dev., 2011)

Vapourtec Ltd.

Chemtrix BV